The effect of online reputation systems on intergroup inequality - Judith Kas (Journal of Behavioral and Experimental Economics, 2022)
Recent studies state that online reputation systems may decrease or even eliminate intergroup inequality. These studies base their conclusion on the finding that the presence of reputation information may decrease platform users' reliance on demographic information. However, these findings tell only part of the story of the relation between reputation systems and intergroup inequality: they overlook the problem that reputation systems help those who obtained at least one review but may negatively affect those individuals who have not participated in interactions before. This study is the first to take the endogeneity of the reputation building process into account by providing a direct test of differences in inequality between individuals of different nationality between a situation with and without a reputation system. Using a preregistered online experiment, I show that inequality between American and Indian individuals is not lower when there is a reputation system than when there is no reputation system. Moreover, emergent inequality in initial rounds affects inequality in later rounds. This implies that platforms that wish to create equal opportunities for users with different backgrounds should not only try to make their reputation system more effective, but also to reduce initial differences between individuals with different backgrounds.
Keywords: 300; reputation systems; inequality; discrimination; Trust; cumulative advantage